Preparation and swelling behavior of biodegradable poly(aspartic acid)-based hydrogel - Min, SK; Kim, Soo Hyun; Kim, JH (한국공업화학회, 2000)
High molecular weight polysuccinimide (PSI), as the precursor polymer for water-soluble poly(aspartic acid), was prepared by the thermal polycondensation of L-Aspartic acid. The molecular weight, estimated from the solution viscosity of the PSI, was within a range of 100000 similar to 140000 Dalton. A crosslinked gel powder was prepared by the thermal curing reaction of a freeze-dried mixture composed of polyaspartic acid and a proper amount of PEG-diepoxide in water. The dependences of swelling behavior on the composition and curing conditions were also investigated.